If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9 + -1x)(3x + 5) = 0 Reorder the terms: (9 + -1x)(5 + 3x) = 0 Multiply (9 + -1x) * (5 + 3x) (9(5 + 3x) + -1x * (5 + 3x)) = 0 ((5 * 9 + 3x * 9) + -1x * (5 + 3x)) = 0 ((45 + 27x) + -1x * (5 + 3x)) = 0 (45 + 27x + (5 * -1x + 3x * -1x)) = 0 (45 + 27x + (-5x + -3x2)) = 0 Combine like terms: 27x + -5x = 22x (45 + 22x + -3x2) = 0 Solving 45 + 22x + -3x2 = 0 Solving for variable 'x'. Factor a trinomial. (9 + -1x)(5 + 3x) = 0Subproblem 1
Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9Subproblem 2
Set the factor '(5 + 3x)' equal to zero and attempt to solve: Simplifying 5 + 3x = 0 Solving 5 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 0 + -5 3x = 0 + -5 Combine like terms: 0 + -5 = -5 3x = -5 Divide each side by '3'. x = -1.666666667 Simplifying x = -1.666666667Solution
x = {9, -1.666666667}
| -x-18+2x+4=6x+24 | | a-6b+2c+a-6b+n-2c= | | 9y+3=27 | | 4b+25=9b | | 6(4-1)-5(z+8)=16(z+1) | | y=-(1)-3 | | y=-(0)-3 | | y=-(-1)-3 | | 4b+5x=2x | | -8(t-5)-(t+4)=9 | | 2x+10=27 | | 7.7(-9+2x)=-49 | | y=6(5)-8 | | x=9x-12 | | y=6(1)-8 | | 12(2x-5)=24x+16 | | -(3y+2)-(-2y-8)=5 | | y=6(-1)-8 | | 6+2(x-1)=1-3(x-6) | | 4+6(x-2)=1-5(x-1) | | -49=3x+3x-7 | | -(4y+1)-(-3y-6)=4 | | 12+-2a=2 | | 9ln(8x)=54 | | 2y+10(2)=-16 | | 2y+10(-3)=-16 | | -8+2x-4x=-18 | | -5(3n+2)=10 | | ln(x)+ln(x+4)=0 | | 15y-3=29-y | | 17b-8=0 | | x-18+2(x+2)=6x+24 |